The Effect Of Rondo Training Model On Passing Ability In Futsal Games Of State Senior High School 2 Takalar - Achmad Karim (Journal Physical Health Recreation (JPHR), 2025)
This research is an experimental research that aims to determine the Effect of Rondo Training Model on Passing Ability in futsal game of SMA Negeri 2 Takalar. The independent variable in this study is the rondo training model while the dependent variable is the short pass test. The population in this study was 50 students of SMA Negeri 2 Takalar. Sampling using categorization technique with a sample size of 20 students. The research data was obtained using a test (pre-test and post-test). The data analysis technique used is statistics using computer facilities through the SPSS program with prerequisite tests, namely the normality test and the t-test using the paired sample t-test. Based on the results obtained, the normality test of the pretest data sig 0.090 and the posttest obtained sig. 0.067. Sig> 0.005 then the pretest and posttest data are normal. After conducting a significance test using the paired sample t-test, the calculated t = 6.030 and sig 0.005 (P <0.05) were obtained, so H0 was rejected and H1 was accepted, meaning that there was a significant influence of the rondo training model on the passing ability of the futsal game at SMA Negeri 2 Takalar.